Biomechanical analysis on change of toe-out angle in squat - Song, H. K.; So, J. M. (Korean Journal of Sport Biomechanics, 2019)
Objective: The aim of this study was to suggest correct and effective way of squat through biomechanical analysis variables on the change of the toe-out angle. Method: 7 high school male weightlifter (age: 17.57±0.53yrs, height: 174.0±3.93cm, weight: 81.0±9.17kg, 1RM: 164.29±2.7kg) participated in this study. Results: Angle of the hip joint at E2 was smaller than toe-out angle was in 20°than in 0° (p10°than n 30° (p30°than in 0° (p30°. In average iEMG of flexion phase, extension phase and in peak iEMG, RF of right leg, VM and VL of left leg showed high activity at all of the toe-out angles. In average iEMG of flexion phase, extension phase and in peak iEMG, all of the muscles activity of right leg showed high in 10° and low in 0°, 30°. Conclusion: It is judged that setting the toe-out angle 10° in squat help to efficiently use muscles and ensure stability.